Human buccal epithelium cell response to low intensive neutron radiation - K. A. Kuznetsov; P. S. Kyzym; A. Yu. Berezhnoy; A. F. Shchus; G. M. Onishchenko; Yu. G. Shckorbatov (Біофізичний вісник, 2018)
Background: The investigation of the low doses of ionizing radiation is still a great importance for identification of the threshold of harmful effect and potential hormetic effect of low doses.